2011
DOI: 10.33549/physiolres.932110
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death Thirty Years Ago and at Present. The Role of Autonomic Disturbances in Acute Myocardial Infarction Revisited

Abstract: The most common cause of sudden cardiac death is ventricular fibrillation (VF). In addition to the status, size and location of the ventricular focus, a major pathogenic mechanism triggering VF is autonomic dysbalance (disturbance). This term refers to a wide range of reflex changes in the ratio of sympathetic to vagal ventricular activation over time, occurring immediately after coronary artery occlusion at the onset of acute myocardial infarction (AMI). Another trigger of VF is autonomic disturbance due to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, there is a growing recognition of increased cardiovascular risk among human HIV‐infected patients . It is well established that autonomic dysfunction plays an important role in the occurrence of cardiovascular morbidity and mortality . Few studies have assessed the autonomic function in cART‐receiving HIV‐infected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a growing recognition of increased cardiovascular risk among human HIV‐infected patients . It is well established that autonomic dysfunction plays an important role in the occurrence of cardiovascular morbidity and mortality . Few studies have assessed the autonomic function in cART‐receiving HIV‐infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sudden cardiac arrest contributes to most cardiac deaths in HIV‐infected patients with a rate more than four times expected in the general population with similar risk factors . It has been suggested that autonomic dysfunction may be the mechanism underlying sudden cardiac death in this group of patients . Previous small studies have demonstrated the presence of autonomic dysfunction in untreated HIV‐infected patients .…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms can reflect such autonomic unbalance, including alterations in the synthesis/release of neurotransmitters (Penido et al, 2012 ) and morphological damage in CNS circuitry recruited in the genesis and/or modulation of autonomic activity (Plagemann et al, 2000 ; Pinos et al, 2011 ). It is well established that chronic cardiac sympathetic activation raises the sudden death risk (Schultz and Li, 2007 ; Pokorný et al, 2011 ) and malnutrition could trigger cardiovascular disturbances (Sawaya et al, 2005 ), highlighting the fundamental importance of keeping investigate the autonomic balance in protein-deprived situation.…”
Section: The Influence Of Post-weaning Low-protein Diet On Sympathetimentioning
confidence: 99%
“…In these patients, underlying ionic current abnormalities, particularly those mediating repolarization, either co-exist with and/or are exacerbated by autonomic imbalances favoring enhanced sympathetic drive (e.g., Chen et al, 2007 ; Pokornı et al, 2011 ; Wellens et al, 2014 ). As such, multi-modality stratifications techniques, encompassing electrocardiographic evaluation of repolarization abnormalities during states of autonomic activation, such as exercise, are favored (Goldberger et al, 2014 ; Wellens et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%